2018
DOI: 10.17679/inuefd.346720
|View full text |Cite
|
Sign up to set email alerts
|

9-12 Yaş Çocukların Estetik Değer Algılarının İncelenmesi

Abstract: The aim of the research is to examine the aesthetic value perceptions of children aged 9-12 years. The study was conducted with a total of 1021 (534 female, 487 male) students in the Black Sea Region, aged 9-12 years. The research was conducted with convergent parallel design from mixed method research designs. The art and aesthetic value attitude scale developed by Mazman Budak (2012) and metaphor data collection form was used as means of collecting data. The results of the research showed that female student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…This may be due to the fact that women have a higher aesthetic perception than men and that women make more careful observations and attribute different meanings to objects or beings around them. As a matter of fact, Demirel (2018) states that females' views and awareness of the artistic and cultural beauties observed in their environment are more positive than males. Within the scope of the research findings, the following suggestions were developed:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the fact that women have a higher aesthetic perception than men and that women make more careful observations and attribute different meanings to objects or beings around them. As a matter of fact, Demirel (2018) states that females' views and awareness of the artistic and cultural beauties observed in their environment are more positive than males. Within the scope of the research findings, the following suggestions were developed:…”
Section: Resultsmentioning
confidence: 99%
“…Diğer bir deyişle metafor ded kendisini üretenin tutumları, duyguları ve değerlendirmeleriyle uyumlu olduğundan onu geliştirenin sosyal kimliği hakkında da perspektif sunar. Demirel (2018), Kılcan ve Akbaba'nın (2014) çalışmasına benzer bir şekilde 9-12 yaş çocuklarının estetik kavramını genel olarak cerrahi bir müdahale, fiziksel görünüm ya da esneklik olarak algıladıklarını ifade etmektedir. Aynı çalışmada estetik kavramı, cerrahi müdahele kategorisinde "estetik ameliyat" (156), fiziksel görünüm kategorisinde "güzellik", doğa güzelliği kategorisinde "çiçek" (46) ve esneklik kategorisinde "lastik" (35) metaforu ile tanımlanmıştır.…”
Section: Sonuç Ve öNerilerunclassified
“…Among these concepts, it is seen that the concepts of beautiful/beauty (f=15), nose (f=14), and appearance (f=9), which are determined to be used only in the same context with the external appearance of the person and the surgical operation, come to the fore. It may be expected that the concept of aesthetics is perceived in this way by people who do not have a professional interest or relationship with art or who are in younger age groups: Demirel (2018), in his study with children aged 9-12, concluded that although the participants associated the concept of aesthetics with beauty, this association generally included surgical intervention and physical appearance, and he commented that they could not "assimilate" aesthetics artistically. Similarly, Kılcan and Akbaba (2014) in their research with eighth-grade students, one of the findings they reached in line with the analysis of the metaphors developed regarding aesthetics and the analysis of the drawings, is that the students perceive aesthetics as a surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Bu kavramlar arasında yalnızca kişilerin dış görüntüleriyle ve cerrahi operasyonla aynı bağlam içerisinde kullanıldığı belirlenen güzel/güzellik (f=15), burun (f=14) ve görünüm/görünüş (f=9) kavramlarının öne çıktığı görülmektedir. Sanatla mesleki bir ilgi ve ilişkisi bulunmayan ya da küçük yaş gruplarındaki kişilerce estetik kavramının bu yönde algılanması beklendik olabilir ve bu yönde bulgulara ulaşan ilgili çalışmalar da (Demirel, 2018;Kılcan & Akbaba, 2014) bulunmaktadır. Ancak lisans düzeyinde mesleki müzik eğitimi alan kişilerin, azımsanamayacak bir çoğunlukta bu yönde bir estetik algıya sahip olmaları oldukça düşündürücüdür.…”
Section: Tartışma Ve Sonuçunclassified
“…Art education is determined to be an integral part of general education and its implementation is also the responsibility of intellectuals. By the immortalization of culture and art civilization; it engraves a rich transformation of consciousness to the child (Bae, 2017;Demirel, 2018).…”
Section: Introductionmentioning
confidence: 99%